2022
DOI: 10.1097/mbp.0000000000000578
|View full text |Cite
|
Sign up to set email alerts
|

Effects of uric acid-lowering therapy in patients with essential arterial hypertension

Abstract: BackgroundAsymptomatic hyperuricemia (AHU) is de ned as elevated serum uric acid (UA) concentration without symptoms. This study aimed to determine the effects of AHU treatment with allopurinol on selected hypertension mediated organ damage (HMOD) indices in patients with uncomplicated essential arterial hypertension (AH). MethodsPatients aged 30-70 years with AHU and essential hypertension grade 1-2 with adequate blood pressure (BP) control, without previous urate lowering therapy (ULT) were divided into two … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
4
0
1
Order By: Relevance
“…The incriminated pathways are activation of epithelial- and endothelial-to-mesenchymal transition (EMT, EndoMT), which will activate fibroblasts and myofibroblasts and subsequent renal fibrosis [ 25 ]. Other studies associate inflammation markers, such as C-reactive protein (CRP) or TNF-alfa, as directly proportional with serum UA concentrations [ 61 , 62 ]. Some researchers consider that serum UA can be a strong predictor of acute kidney injury without correlation with the baseline renal function [ 63 ].…”
Section: Pathogenic Potential Of Serum Uric Acid In Renal Impairmentmentioning
confidence: 99%
“…The incriminated pathways are activation of epithelial- and endothelial-to-mesenchymal transition (EMT, EndoMT), which will activate fibroblasts and myofibroblasts and subsequent renal fibrosis [ 25 ]. Other studies associate inflammation markers, such as C-reactive protein (CRP) or TNF-alfa, as directly proportional with serum UA concentrations [ 61 , 62 ]. Some researchers consider that serum UA can be a strong predictor of acute kidney injury without correlation with the baseline renal function [ 63 ].…”
Section: Pathogenic Potential Of Serum Uric Acid In Renal Impairmentmentioning
confidence: 99%
“…Taken together, therefore, a linking mechanism between Ow/Ob-associated CRP levels and HMOD-HRC in hypertensive patients seems likely. The fact that reduction in inflammation, evaluated by CRP levels, has been associated with a reduction in HMOD with uric-acid-lowering therapy in patients with essential hypertension [35] supports this hypothesis. Further large prospective intervention studies are needed to demonstrate that advocating ideal CVHM may decrease hs-CRP, leading to prevention of hypertension-related complications.…”
Section: Comparison With Previous Studies and Risk Factors Including ...mentioning
confidence: 81%
“…A cohort study involving 100 participants with asymptomatic hyperuricemia revealed that, compared with HCs, those receiving allopurinol experienced significant reductions in office systolic and diastolic blood pressure, central systolic blood pressure, pulse pressure, carotid intima-media thickness, and hs-CRP. These improvements are indicative of a positive impact on a patient's long-term prognosis ( 34 ). Furthermore, a meta-analysis of seven eligible trials involving 503 participants with hyperuricemia demonstrated that urate-lowering therapy led to decreases in systolic and diastolic blood pressure, fasting insulin levels, and homeostasis model assessment of insulin resistance ( 35 ).…”
Section: Discussionmentioning
confidence: 99%